2019
DOI: 10.1186/s12903-019-0775-8
|View full text |Cite
|
Sign up to set email alerts
|

Oral Candidal carriage and associated risk indicators among adults in Sakaka, Saudi Arabia

Abstract: Background Candida is a ubiquitous organism in nature which inhabits the oral cavity as part of the normal microbial flora. The oral carriage of Candida is perpetuated by several predisposing factors. Methods This cross-sectional study was designed to investigate the carriage rate of Candida among 104 voluntary adults at the college of medicine - Jouf University. The concentrated oral rinse technique u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
2
12
2
Order By: Relevance
“…Eighty percent (80%) of our sample were expatriates living in the United Arab Emirates (UAE), which is representative of the country’s population profile whereby only 13% of the population are UAE nationals. The prevalence of Candida species reported here is lower than that reported in nearby Saudi Arabia by Alrayyes et al [ 16 ] and Darwazeh et al [ 21 ] where they found the prevalence to be 43.4% and 52%, respectively. Diversity in the prevalence of Candida carriage is commonly observed and has been attributed to many overlapping local and systemic factors in the studied population.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Eighty percent (80%) of our sample were expatriates living in the United Arab Emirates (UAE), which is representative of the country’s population profile whereby only 13% of the population are UAE nationals. The prevalence of Candida species reported here is lower than that reported in nearby Saudi Arabia by Alrayyes et al [ 16 ] and Darwazeh et al [ 21 ] where they found the prevalence to be 43.4% and 52%, respectively. Diversity in the prevalence of Candida carriage is commonly observed and has been attributed to many overlapping local and systemic factors in the studied population.…”
Section: Discussioncontrasting
confidence: 82%
“…Attempts to control dental caries necessitates a good understanding of the aetiological factors that favour the growth of both cariogenic bacteria and Candida . Despite the wide diversity of those aetiological factors, two are considered to be among the most influential: poor oral hygiene and diabetes mellitus [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most species cannot live at the temperature of the human body [ 2 , 3 ], so only a limited number of Candida species harmlessly live in the healthy mouth, eyes, gastrointestinal tract, vagina, and skin [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The prevalence of Candida albicans ( C. albicans ) isolated from the oral cavity are reported to be around 30% to 50% of the healthy general population, 50–65% of people who wear dentures, 65–88% of people who reside in long term care facilities, and 90–95% of individuals with human immunodeficiency virus (HIV) infection and also in patients who receive corticosteroid, chemotherapy, immunosuppressant, or radiation for head and neck cancers [ 1 , 2 , 4 , 10 , 11 , 12 , 13 ]. When an imbalance in the normal oral flora or inadequate immune defense occurs, Candida can overgrow to induce a fungal infection called oral candidosis or thrush.…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent have been C. glabrata and C. parapsilosis, followed by C. tropicalis and C. Krusei . The four Candida species plus C. albicans account for more than 90% of cases of oral or disseminated candidosis and candidemia [ 5 , 6 , 7 , 8 , 9 , 10 ]. This shift in species with a higher incidence of candidosis caused by NAC species has emerged as a major bearing on the morbidity and management of patients who are cared for in intensive care units (ICUs) or have important risk factors, such as hematologic malignancies, transplants, major abdominal surgery, and/or prolonged treatment with corticosteroid, as the increasing antifungal resistance along with a wide range of minimum inhibitory concentrations (MICs) to fluconazole between Candida species exists [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Candida albicans is the most common species of Candida found in the oral cavity, being present in 30%–50% of the people with varying carriage. [ 3 4 ] The oral carriage of Candida ranges from 3%–75% owing to factors such as age, smoking, gender, oral hygiene status, and association of systemic diseases[ 5 ] to name a few.…”
Section: Introductionmentioning
confidence: 99%